Bank service quality perceptions of business customers: Priorities for banks in resource allocations in an e-banking context - Wong, David; Rexha, Nexhmi (School of Marketing, Curtin Business School, 2007)
The onset of electronic commerce as a major tool of business has brought with it new methods of doing business and a redefinition of the relationship between an organisation and its customers. To deal with such a situation, organisations need to review the service quality expectations of their customers and how the performance of their services measure up to these expectations. This is particularly relevant in the banking sector, where the emergence of electronic banking brings with it a new avenue for banks to be more competitive through decreasing costs and broadening market reach. To realise these benefits, banks must be successful in providing high levels of service quality in order to be able to divert more of their customers to these low cost methods of banking. This research provides a review of how service quality perceptions have evolved in the banking sector amid the changes brought about by electronic banking. The SERVQUAL scale for measuring service quality that has been used for up to 20 years is employed in this research. Factor analysis of the results reconfirms the robustness and continued usefulness of this scale, and the results from this research are compared to past research. It was found that large discrepancies exist between customer expectations and their perceived performance of banking services. Quadrant analysis was used to analyse these discrepancies across the five dimensions of service quality and provided specific recommendations on how banks should prioritise the allocation of their resource to maintain high perceived service quality.